Basic Characteristics and Industrial Application of Styrene Copolymer-Based Thermoplastic Elastomers (Overview) - Talanyuk, V. V.; Shadrin, A. O.; Yurzhenko, M. V. (Київський національний університет імені Тараса Шевченка, 2019)
Thermoplastic elastomers (TPEs) have elastic properties that are similar to rubber but capable of melting and all thermoplastic properties. Block copolymers are also widely used, in which there are links of different polymers in the structure of their macromolecules. So styrene-ethylene-butylene- styrene (SEBS) belongs to the second generation, the products of which have high physical and mechanical properties, and biocompatibility allows it to be used in the medical field. The main characteristics and analysis of advantages of TPE on the example of SBSS in comparison with traditional materials are presented in the paper.Key words: thermoplastic elastomers, SEBS, structure, properties, application.Pages of the article in the issue: 98 - 103Language of the article: Ukrainian